2018
DOI: 10.29252/jhsme.5.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Halal Brand Is an Effective Solution for the Development of Medical Tourism: A Case Study of Hospital Hotel

Abstract: Background and Objectives: Halal branding covers a wide range of economic activities including pharmaceuticals, cosmetics, health, textiles, clothing, leather, financial services, banking and tourism. Among the various forms of tourism, medical tourism has grown rapidly due to its competitive advantages. Therefore, the purpose of this study is to investigate halal branding as a strategy to develop medical tourism. Methods: A qualitative research method and a case study were used. Data were drawn from semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The situation of health services in hospitals in Indonesia is the same as health services in Malaysia which have compared services as Halal healthcare services, including providing halal food, providing providers or health workers according to patient gender, and providing places of prayers for patients and families [2]. At present, the concept of "hotel hospital" that is close to Islamic teachings has been developed as a medical tourism approach where patients and families stay close, and the daily atmosphere at home includes conducting 5 times prayer according to Islamic teaching [9]. Hospitals in the two provinces in this study have the potential and strength to be developed into Halal healthcare tourism which will have a positive impact on the country's revenue, service quality, and recognition of Indonesia in the world.…”
Section: Her Background Is Indeed From Due To Coincidence the Head Of The Nursing Field Was Female And Indeed He Was More Sharia In Termsmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation of health services in hospitals in Indonesia is the same as health services in Malaysia which have compared services as Halal healthcare services, including providing halal food, providing providers or health workers according to patient gender, and providing places of prayers for patients and families [2]. At present, the concept of "hotel hospital" that is close to Islamic teachings has been developed as a medical tourism approach where patients and families stay close, and the daily atmosphere at home includes conducting 5 times prayer according to Islamic teaching [9]. Hospitals in the two provinces in this study have the potential and strength to be developed into Halal healthcare tourism which will have a positive impact on the country's revenue, service quality, and recognition of Indonesia in the world.…”
Section: Her Background Is Indeed From Due To Coincidence the Head Of The Nursing Field Was Female And Indeed He Was More Sharia In Termsmentioning
confidence: 99%
“…Health tourism has been targeted by neighboring countries such as Thailand, Singapore, Malaysia, and India from decades ago [8]. At present the medical tourism trend is starting to develop to the target sharia market, or what is known as Halal medical tourism, Halal healthcare tourism, or Sharia health tourism [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halal medical tourism has high growth potential given the fact that Muslims make up a quarter of the global population and will continue to show increases (Alfarajat, 2022). Arefi et al (2018) explain that halal tourism itself has been shown to make a significant contribution to economic growth both in Indonesia and in other countries. Still in the context of Muslim tourism, brand perception and customer satisfaction play a crucial role in efforts to attract Muslim medical tourists.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the medical tourism sector is one of the important sectors that requires innovative practices to address the various challenges faced by the health and tourism industries. Not only that, management of knowledge-based assets focused on developing Muslim Friendly Medical Tourism (MFMT) is also an important requirement that must be considered in the context of the related tourism sector (Arefi et al, 2018;Hamzah et al, 2022;Alfarajat, 2022). Overall, halal medical tourism presents opportunities for the development of halal branding, market growth, and economic growth.…”
Section: Introductionmentioning
confidence: 99%